2019
DOI: 10.1186/s12917-019-1915-8
|View full text |Cite
|
Sign up to set email alerts
|

A double-blinded randomised dietary supplement crossover trial design to investigate the short-term influence of medium chain fatty acid (MCT) supplement on canine idiopathic epilepsy: study protocol

Abstract: Background Epilepsy is the most common brain disease in dogs. Recently, diets have been reported to have a positive impact on seizure activity and behaviour in various species including dogs with idiopathic epilepsy (IE). Historically, classic high fat ketogenic diets (KD) and medium chain triglycerides (MCT) KD have been successfully used to manage drug-resistant epilepsy. Similarly, an MCT enriched diet has been shown to improve seizure control and behavioural comorbidities in some dogs with IE.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 107 publications
0
16
0
Order By: Relevance
“…The study design has been published separately 44 . In brief, the main study hypothesis was that MCTs administered as a DS would reduce seizure frequency.…”
Section: Methodsmentioning
confidence: 99%
“…The study design has been published separately 44 . In brief, the main study hypothesis was that MCTs administered as a DS would reduce seizure frequency.…”
Section: Methodsmentioning
confidence: 99%
“…Nine of 21 dogs (43%) had more than 50% reduction in seizure frequency, including two dogs becoming seizure‐free 101 . In a recently published multicenter randomized double‐blinded crossover study, dog owners were taught to add MCT oil (contributing 9% daily energy) containing 50%–65% octanoate and 30%–50% decanoate versus colorless, extra virgin olive oil to their dogs' regular food for a total of 28 dogs 102,103 . The case number chosen for this study was based on the results of Law et al, 99 who used a similar study design 102,103 .…”
Section: Anticonvulsant Effects Of Mctsmentioning
confidence: 99%
“… 101 In a recently published multicenter randomized double‐blinded crossover study, dog owners were taught to add MCT oil (contributing 9% daily energy) containing 50%–65% octanoate and 30%–50% decanoate versus colorless, extra virgin olive oil to their dogs' regular food for a total of 28 dogs. 102 , 103 The case number chosen for this study was based on the results of Law et al, 99 who used a similar study design. 102 , 103 A power analysis was performed and indicated that 22 dogs would be sufficient using Wilcoxon signed ranked test to reach a power of .95 (90%) at Type I error rate of .05 (PASS V19.02, NCSS, Statistical Software).…”
Section: Anticonvulsant Effects Of Mctsmentioning
confidence: 99%
See 1 more Smart Citation
“…Around 0.6% of the dog population and up to 18.3% of dogs of specific breeds are affected by epilepsy (14)(15)(16). There are several studies about quality of life (QoL) in canine patients with epilepsy (17)(18)(19)(20), but sudden unexpected death in dogs is only sporadically reported and poorly studied (21)(22)(23)(24). Idiopathic epilepsy (IE) is described as an exclusion diagnosis for dogs of a certain age group with recurrent seizures without an underlying structural cause, but with a (presumed) genetic influence (25,26).…”
Section: Introductionmentioning
confidence: 99%